Transoral laser microsurgery for treatment of oropharyngeal cancer in 368 patients. Issue 9 (10th June 2019) - Weiss, Bernhard G.; Ihler, Friedrich; Anczykowski, Mahalia Zoe; Bertlich, Mattis; Kitz, Julia; Steiner, Wolfgang; Canis, Martin; Jakob, Mark
Abstract: Background: Oncological and functional outcome of transoral laser microsurgery (TLM) for primary treatment of oropharyngeal cancer was examined using a multimodal treatment concept. Methods: A total of 368 patients with oropharyngeal squamous cell carcinoma (pT1‐4, pN0‐2, M0) underwent TLM +/− neck dissection (85%), +/− (chemo)radiotherapy (57%). The majority of patients had advanced stage III and IVa disease (79%). Results: Five‐year Kaplan‐Meier estimates for local control were 83.5% for pT1, 74.1% for pT2, 77.3% for pT3, and 76.0% for pT4a tumors. Five‐year estimates of overall, disease‐specific, and recurrence‐free survival for stage I were 76.0%, 92.8%, and 69.1%; for stage II 71.1%, 85.7%, and 49.6%; for stage III 61.7%, 72.5%, and 58.8%; and for stage IVa 57.3%, 73.7%, and 63.9%, respectively. Postoperative (chemo)radiotherapy improved the outcome for advanced disease. p16‐positive tumors had superior survival estimates. Overall, 93.5% maintained regular oral nutrition without feeding tube dependency. Conclusion: Primary TLM in multimodal concepts of treatment offers good oncologic outcome even for advanced‐stage oropharyngeal cancer.